2000
DOI: 10.1053/jhep.2000.18425
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes in Hepatocellular Dysplastic Nodules on Microdissected Liver Biopsies

Abstract: The genetic profile of dysplastic hepatocellular nodules arising in cirrhosis is poorly understood. We assessed loss of heterozygosity (LOH) and microsatellite instability (MI) in 10 dysplastic nodules (4 low-grade and 6 high-grade) with surrounding cirrhosis and in 10 hepatocellular carcinomas (HCC). Six microsatellite loci were selected and investigated on microdissected needle biopsies. Twenty-four (24.4%) informative loci showed allelic loss, while MI was seen in 3 loci only (3%). The most involved sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 29 publications
(39 reference statements)
5
38
1
3
Order By: Relevance
“…This low incidence of allelic losses was consistent with those in previous reports (11,13,18) and also our previous report on mostly HBVassociated cirrhotic livers but with concomitant HCC (17). From the previous reported series, the FAL indices in cirrhosis vary from 0.05 to 0.15 (11,13,18). The etiologies in the previous studies consisted of a mixture of both chronic HBV and HCV infection, with HBV-associated cirrhosis ranging from 21% to 44% of their cases and HCV-associated cirrhosis ranging from 33% to 55%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This low incidence of allelic losses was consistent with those in previous reports (11,13,18) and also our previous report on mostly HBVassociated cirrhotic livers but with concomitant HCC (17). From the previous reported series, the FAL indices in cirrhosis vary from 0.05 to 0.15 (11,13,18). The etiologies in the previous studies consisted of a mixture of both chronic HBV and HCV infection, with HBV-associated cirrhosis ranging from 21% to 44% of their cases and HCV-associated cirrhosis ranging from 33% to 55%.…”
Section: Discussionsupporting
confidence: 93%
“…Although LOH was observed at z1 of the 19 loci in 70.8% of the cirrhotic livers, the mean FAL index was low, at 0.09. This low incidence of allelic losses was consistent with those in previous reports (11,13,18) and also our previous report on mostly HBVassociated cirrhotic livers but with concomitant HCC (17). From the previous reported series, the FAL indices in cirrhosis vary from 0.05 to 0.15 (11,13,18).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed we found that most cirrhoses and the vast majority of malignant tumors had promoter methylation affecting at least a single gene. Thus, in addition to well-recognized molecular abnormalities such as loss of heterozygosity, deletion, and point mutation, [16][17][18][19][20] inactivation of cell cycle inhibitors by epigenetic mechanisms seems to play an important role in human hepatocarcinogenesis. We have also found that methylated cirrhosis usually associates to methylated HCC, suggesting a common mechanism of gene inactivation from cirrhosis to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…28 In the current investigation, the 1p36-p34 region was explored in more detail to identify new early deletions in human hepatocarcinogenesis. D1S2843 (1p36.12) and D1S513 (1p34.3) were found to be more frequently deleted than the other loci in HCCs, DNs, and CNs adjacent to them.…”
Section: Discussionmentioning
confidence: 99%